Size and Distribution of Bivalva in the Interidal Zone in Sambungo Village, Silaut District, Pesisir Selatan Regency, West Sumatera Province - Silaban, Tulus Gandra Saputra; Tanjung, Afrizal; Siregar, Yusni Ikhwan (Journal of Coastal and Ocean Sciences, 2022)
This research was carried out in January 2021 in the Intertidal Zone of Sambungo Village, Silaut District, Pesisir Selatan Regency, West Sumatra Province. The purpose of this study was to determine the size variation of the bivalve, the distribution pattern of the bivalve, the effect of the type of sediment fraction on the size, and the distribution of the bivalve in the intertidal zone. The method used in this research is a survey method which is carried out by direct observation and sampling in the field. Bivalve samples obtained were identified at the Marine Biology Laboratory and Sediment Fraction Analysis was carried out at the Chemical Analysis Laboratory, Faculty of Fisheries and Marine, Universitas Riau. Based on the results of the study, the highest number of bivalves was at station 1 as many as 11 individuals. The distribution pattern of macrozoobenthos in the intertidal zone of Sambungo Village ranges from 3.86 to 5.07 with the highest morisita index value being at station 1. The highest percentage of sediment fraction is 96.53% in the lower zone and the highest organic matter content is at station 1 of the lower zone. with a total percentage of 6.65%. Based on the criteria for the morisita index at station 1, station 2, and station 3 with an Id>1 value, it can be concluded that the distribution of Bivalvia in the intertidal zone in Sambungo Village is clustered.